Water Security and River Basin Revitalization of the São Franciscos River Basin: A symbiotic Relationship - Alves da Silva Rosa, Larissa (2021)
What is river basin revitalization’s place in relation to water security? This question is the basis of our reflection, posed to help in the understanding of the evolution of both concepts, taking management of the São Francisco River Basin (Brazil) as a case study. With this main objective in mind, a literature review was carried out, followed by the collection of survey data on the watershed’s revitalization program. In this context, the members of the São Francisco River Basin Committee (a total of 124 participants) were consulted, using questionnaires with the Delphi method. The respondents (a total of 47) chose the river basin revitalization strategy as the main measure to achieving water security in the São Francisco River Basin. They also highlighted the importance of the environmental dimension, underlining measures for conservation and restoration of the ecosystem’s natural functions. The concept map tool was adopted for a comparative perspective between conceptual implications of revitalization and water security for the studied river basin’s conservation. The results showed the existence of a symbiotic relationship between both concepts. Consequently, we conclude that it is urgent to reconcile water use and ecosystem ecological integrity through the comprehensive concept of water security